Fast-Lock Low -Jitter Delay Locked Loop - Soh, Lip Kai (2007)
In this thesis, an improved phase frequency detector (PFD) and dual charge pump architecture for fast-lock low -jitter delay-locked loop (DLL) is proposed and analyzed.